Concept of Revenue, Expenses and Liabilities in Accounting for Zakat, Waqf and Baitulmal in Malaysia: An Analysis from Shariah Perspective - Marina Abu Bakar (Center of Strategic Studies (PUSKAS) BAZNAS, 2018)
Revenue, expenses and liabilities are an important concept in current accounting practices. These concepts are applied in accounting standards where this standard serves as a guideline for a company or organization in preparing and presenting income, expenses, assets and liabilities in accordance with the standards set by the International Accounting Standards Board (IASB). The accounting standards issued by this international body refer to conventional accounting standards. In Malaysia, the State Islamic Religious Council (MAIN) as the trustee for Zakat, Waqf and Baitulmal uses standards issued by the Malaysian Accounting Standards Board, Private Entity Reporting Standards (PERS) and best practice guidelines by the National Audit Department (Malaysia) (JANM). These two documents are used as references in the preparation of financial reporting for MAIN. However, there are problems in terms of implementing these concepts for Zakat, Waqf and Baitulmal with current accounting standards. This is because current accounting practices are different from the concepts of revenue, expenses and liabilities adopted by Zakat, Waqf and Baitulmal according to Islamic law. This study aims to analyze the concept of revenue, expenses and liabilities in Zakat, Waqf and Baitulmal accounting from Shariah perspective. The design of this study is qualitative. The method of content analysis was used to analyze data from sources such as classical Fiqh books. The findings show that there is a difference between the concept of revenue, expenses and liabilities in Zakat, Waqf and Baitulmal accounting in the Islamic context. The study is expected to help the parties involved to develop accounting standards for zakat, waqf and baitulmal which are compliant with Shariah.